2010
DOI: 10.4314/ejhd.v24i1.62942
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adolescent fertility in Ethiopia

Abstract: Background: Worldwide, adolescents suffer from a disproportionate share of reproductive health problem. Throughout the world, over 14 million adolescents aged 15-19 years give birth annually. The purpose of this study was to assess the level and identify proximate and other determinants of adolescent fertility in Ethiopia. Methods: Raw data collected from all part of the country using stratified cluster sampling method by the Ethiopian Demographic Health Survey 2005 (EDHS-2005) was used. After the data for ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
59
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 12 publications
31
59
1
3
Order By: Relevance
“…This might be explained by the fact that women with early birth have many years remaining to stop child bearing or to reach the age when reproduction ends. This finding is similar with previous reports from Africa [14,[23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This might be explained by the fact that women with early birth have many years remaining to stop child bearing or to reach the age when reproduction ends. This finding is similar with previous reports from Africa [14,[23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…The District is bordered from east, north, south, and west by Afar region, KilleteAwulaelo Woreda, Hintalo-wajirat, Saharti-Samire Woreda and Degua-Temben Woreda respectively. The number of women aged 15-49 years was 23.5% (25,086) of the total population [12]. Regarding the health care service, it had six health centers and thirteen health posts both providing maternal and child health care service.…”
Section: Study Setting and Periodmentioning
confidence: 99%
“…From the descriptive part of this study it is observed that 85.6 percent of adolescent rural women had not given birth and another 14.4 percent had given birth, at the time of the survey. [7] reported that the proportion of teenagers that had given birth at least once prior to the survey at the time of interview were 13.6%.…”
Section: Discussionmentioning
confidence: 99%
“…12 percent of women aged 15 -19 have already started childbearing; 10 percent have had a live birth, and 2 percent are pregnant with their first child [6]. The study suggested that teenagers whose age was between 18 and 19 years were about eight times more likely to be fertile than the younger ones [7]. As the age increases, the risk of exposure to pregnancy and childbearing also increases, because of higher probability of getting sexual relation and marriage.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the world, over 14 million adolescents aged 15-19 years give births annually 35 . It is estimated that, in the last decade, over 58 million girls were married before the age of 18 years; of which, 15 million were 10-14 years old.…”
Section: Adolescent Fertility Ratementioning
confidence: 99%